Penicillin Allergy Evaluation Access: A National Survey. (18th May 2020) - Mancini, Christian M; Fu, Xiaoqing; Zhang, Yuqing; Kuper, Kristi; Schulz, Lucas T; Bhowmick, Tanaya; Postelnick, Michael; Lee, Francesca; Walensky, Rochelle P; Blumenthal, Kimberly G
Abstract: In a study of 121 hospitals from 38 US states, 44% had access to an allergist for inpatient consultations and 39% had access to inpatient penicillin skin testing, indicating that the majority of US hospitals lack sufficient resources to address inpatient penicillin allergies.